El impulso de los programas de cumplimiento normativo: entre la promoción y la imposición - Luyo Castañeda, Michael (2021)
In this article, the author explores the ways in which the Public Administration has been promoting the implementation of regulatory compliance programs in the area of free competition and consumer protection. Thus, he takes as a reference the initially voluntary nature of these programs, and then analyzes the regulatory and jurisprudential treatment in the European Union, the United States, Peru and Chile. Finally, he adopts a critical stance against the imposition of these programs as corrective measures, formulating a series of recommendations for a better performance of the Public Administration.